Prostaglandin F2α Causes Fast Degenerative Changes in Ovulated Mouse Oocytes - Kolarov, A. I; Hadzhinesheva, V. P; Chakarova, I. V; Zhivkova, R. S; Delimitreva, S. M; Markova, M. D; Mourdjeva, M S; Nikolova, V P (Folia biologica (Praha), 2021)
The effects of prostaglandin F2α on the cytoskeleton and membrane organelles of oocytes was investigated by culturing ovulated mouse oocytes in its presence (50 or 100 ng/ml) for 3 h. Tubulin, fibrillar actin, membranes and chromatin were visualized by specific antibodies, phalloidin, lipophilic dye DiOC6 and Hoechst 33342, respectively. Control oocytes were characterized by a meiotic spindle with chromosomes aligned at its equator, and a cortical layer of microfilaments with an actin cap. Intracellular membranes were localized mostly in the central region in metaphase I and in a broader volume, but still excluding the cell periphery, in metaphase II, and were slightly concentrated around the chromosomes. In oocytes treated with 50 ng/ml prostaglandin, cortical actin staining was diminished, the membrane distribution was clustered, and chromosomes showed signs of misalignment despite the apparently preserved spindle. In cells treated with 100 ng/ml prostaglandin, both the spindle and the actin cortex had degenerated or disappeared as microscopic objects. Metaphase plates were on average broader and more disorganized than in the 50 ng/ml group, and the distribution of membrane organelles had become uniform. These effects, to our knowledge observed for the first time, did not require presence of the cumulus during the incubation. They could be regarded as acceleration of the oocyte postovulatory aging, in which cytoskeletal deterioration seemed to have a leading role.
Keywords: aktiny; Mice; oocyty; Dinoprost; metafáze; Actins; meióza; Animals; Metaphase; Meiosis; Oocytes; aparát dělícího vřeténka; Spindle Apparatus; zvířata; dinoprost; myši